2018
DOI: 10.1177/1471301218804727
|View full text |Cite
|
Sign up to set email alerts
|

Assessing implicit and explicit dementia stigma in young adults and care-workers

Abstract: This aim of this study was to assess implicit and self-reported stigma towards people with dementia in young adults with no contact or experience ( n = 23), and in care-workers ( n = 17 professional dementia care-workers). Data were analysed to determine whether stigma was related to self-reported levels of depression, anxiety, stress and professional burnout. Forty participants completed the Implicit Relational Assessment Procedure and Dementia Attitudes Scale. The Depression Anxiety and Stress Scale and Masl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…In Shinan‐Altman, Werner, and Cohen () study, participants expressed negative reactions towards dementia which they believed that contributed to emotional exhaustion. These results are in accordance with other studies which found that higher levels of professional burnout in care workers are associated with higher levels of stigmatizing beliefs and behaviours (Kane et al, ; Kelly & Barnes‐Holmes, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In Shinan‐Altman, Werner, and Cohen () study, participants expressed negative reactions towards dementia which they believed that contributed to emotional exhaustion. These results are in accordance with other studies which found that higher levels of professional burnout in care workers are associated with higher levels of stigmatizing beliefs and behaviours (Kane et al, ; Kelly & Barnes‐Holmes, ).…”
Section: Discussionsupporting
confidence: 92%
“…One of the factors that predispose to stigma was the lower education level. Education and training have been found beneficial in reducing stigma in previous studies (Cullen, Barnes‐Holmes, Barnes‐Holmes, & Stewart, ; Herrmann et al, ; Kaduszkiewicz et al, ; Kane et al, ; Moyle et al, ; Richardson et al, ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations